The long‐term impact of tissue injury on pain processing and modulation: A study on ex‐prisoners of war who underwent torture. (9th September 2013) - Defrin, R.; Ginzburg, K.; Mikulincer, M.; Solomon, Z.
Abstract Background Tissue injury may, in some instances, induce chronic pain lasting for decades. Torture survivors suffer from high rates of chronic pain and hypersensitivity in the previously injured regions. Whether torture survivors display generalized alterations in pain perception and modulation, and whether such alterations underlie their chronic pain is unknown. We aimed at exploring the long‐term alterations in pain perception and modulation in torture survivors. Methods In order to address these questions, a systematic quantitative somatosensory evaluation was performed in individuals (n = 60) who suffer from chronic pain, and who, decades previously, were tortured, resulting in substantial tissue damage. These individuals were compared with age‐ and sex‐matched individuals (n = 44) of similar background. Testing included the measurement of pain threshold and pain tolerance, perceived suprathreshold stimuli, conditioned pain modulation (CPM) and temporal summation of pain (TSP) in intact body regions. Results Chronic pain was found highly prevalent (86.6%) among torture survivors, who exhibited higher suprathreshold pain ratings (p < 0.05), poorer CPM (p < 0.0001) and stronger TSP (p < 0.0001) than controls. Significant differences in CPM and TSP were also found between torture survivors and controls with chronic pain. Chronic pain intensity among torture survivors correlated negatively with the magnitude of CPM (r = −0.47, p < 0.01). Conclusions Torture appears to induce generalized dysfunctional pain modulation that may underlie the intense chronic pain experienced by torture survivors decades after torture. The results may be generalized to instances where chronic pain exists for decades after severe injury in non‐tortured populations and emphasize the importance of preventive care.